Asserting the Ineffable: Rhetorical Appropriation of 'Poetic' and the Contemporary Poetry Text. Issue 2 (August 2017) - Ma, Ming-Qian
Abstract : An elusive, trace-like entity, 'poetic' presents itself in the form of an intangible and yet indispensable relation, or relatedness, in the overall dynamics of information transformation. Paradoxical in nature and function, its ineffability forms the very condition of expressivity in poetry and poetics. 'Poetic', as such, also gains popularity and practicality in popular culture at large where and when it becomes articulated, tailored pragmatically to the specificities of any given activity. As an epochal phenomenon, this pragmatic rendition of 'poetic' takes the more pronounced form of rhetoric, which appropriates 'poetic', and which is resorted to by the contending smaller narratives in the postmodern world as their means for their respective identity formations and legitimations. In the context of the contemporary poetry scene, this rhetorical appropriation of 'poetic' manifests itself eloquently in the three areas of rhetorical situation, constitutive rhetoric, and rhetorical styles, which reveal the mechanisms of a soft interpellation that grants the contemporary poets their identity and legitimacy through their own performative confirmation.